2020
DOI: 10.1371/journal.pone.0239771
|View full text |Cite
|
Sign up to set email alerts
|

Development on Citrus medica infected with ‘Candidatus Liberibacter asiaticus’ has sex-specific and -nonspecific impacts on adult Diaphorina citri and its endosymbionts

Abstract: Huanglongbing (HLB) is a deadly, incurable citrus disease putatively caused by the unculturable bacterium, 'Candidatus Liberibacter asiaticus' (CLas), and transmitted by Diaphorina citri. Prior studies suggest D. citri transmits CLas in a circulative and propagative manner; however, the precise interactions necessary for CLas transmission remain unknown, and the impact of insect sex on D. citri-CLas interactions is poorly understood despite reports of sex-dependent susceptibilities to CLas. We analyzed the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 144 publications
(242 reference statements)
1
8
0
Order By: Relevance
“…The lowest Ct value in CTV detection was 24.82 for male and 26.79 for female, while that in CLas detection was 15.40 for female and 19.05 for male. Several researchers have demonstrated that no differences in acquisiton of CLas between male and female D. citri nor in titers of the bacterium [10][11][12]. In our study, we further con rmed that no signi cant difference existed between male and female in the acquisition rates or titers of CLas and CTV.…”
Section: Resultssupporting
confidence: 79%
“…The lowest Ct value in CTV detection was 24.82 for male and 26.79 for female, while that in CLas detection was 15.40 for female and 19.05 for male. Several researchers have demonstrated that no differences in acquisiton of CLas between male and female D. citri nor in titers of the bacterium [10][11][12]. In our study, we further con rmed that no signi cant difference existed between male and female in the acquisition rates or titers of CLas and CTV.…”
Section: Resultssupporting
confidence: 79%
“… Ning et al (2015) found that the efficiencies of acquisition and transmission of the tomato yellow leaf curl virus (TYLCV) were varied by both biotype and sex. Several other researchers have also concluded that no differences exist in the acquisition or total titer of CLas between male and female D. citri insects ( Ammar et al 2011 , Wu et al 2018 , Coates et al 2020 ). When running electrical penetration graph experiments on healthy ACPs, the effects of sex can be ignored ( Timothy and Michael 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…causing the global pandemic (Bové, 2006;Sétamou et al, 2016;Wang et al, 2017a,b;Kruse et al, 2019;Ammar et al, 2020a,b). The three known Liberibacter species associated with HLB are: Candidatus Liberibacter africanus, CLaf; Candidatus Liberibacter americanus, CLam; and Candidatus Liberibacter asiaticus, CLas (Bové, 2006;Haapalainen, 2014;Wang et al, 2017a,b;Coates et al, 2020). African countries are dominated by CLaf, which is transmitted by two psyllid species, the African citrus psyllid, Trioza erytreae (Hemiptera: Triozidae) and the Asian citrus psyllid (ACP) Diaphorina citri Kuwayama (Hemiptera: Liviidae), which can transmit both CLam and CLas bacteria (Lallemand et al, 1986).…”
Section: Introductionmentioning
confidence: 99%